"Spring is the best time to lose weight": Evidence that dieting is seasonal and reaches peak intensity during Spring. (June 2022) - Griffiths, Scott; Cowley-Court, Tessa; Austen, Emma; Russo-Batterham, Daniel; Blake, Khandis
Abstract: Does dieting intensify during Spring? Previous research suggests that body dissatisfaction is seasonal and peaks during Summer. Extending these findings to seasonal dieting, we contend that individuals' apprehensions about heightened Summertime body dissatisfaction motivate Springtime dieting. To detect seasonal dieting, we examined the seasonal frequencies of 69 dieting hashtags within a database of 564 million tweets originating from the United States and spanning eight calendar years (2012–19). In total, we detected 628, 355 dieting hashtags. Of these, 30% occurred during Spring, 20% during Autumn/Fall, and 25% during each of Summer and Winter. During Spring, there were 64, 000 additional dieting hashtags compared with Autumn/Fall, and 32, 000 additional hashtags compared with Summer and Winter. Of the nine most common dieting hashtags that together accounted for 96% of the total, all nine peaked during Spring ( p s < 0.0001). This Spring-centric pattern was apparent for both appearance-oriented diets (e.g., "atkins" and "weightwatchers") and ostensibly non -appearance-oriented diets (e.g., "vegan" and "glutenfree"), suggesting that non-appearance-oriented diets might nonetheless be co-opted for appearance-oriented purposes. In conclusion, we found credible evidence that dieting intensifies during Spring. Future research should examine whether eating disorders and muscle dysmorphia also intensify during Spring because dieting is intrinsic to both these conditions. Highlights: Seasonal dieting refers to Spring-centric intensification of dieting behaviour. We extracted 625, 000 dieting hashtags on Twitter: 30% occurred during Spring. During Spring, there were 68, 000 additional dieting hashtags versus Autumn/Fall. Appearance-oriented dieting hashtags (e.g., "atkins") peaked during Spring. Non-appearance-oriented dieting hashtags (e.g., "vegan") peaked during Spring.